Does ESG performance promote total factor productivity? Evidence from China - Ma, Jiangming; Gao, Di; Sun, Jing (Frontiers in Ecology and Evolution, 2022)
ESG (environmental, social, and corporate governance) has a significant impact on corporate decision-making. While most studies evidence that ESG significantly improves firm performance and value in long run, few studies quantitatively analyze the linkage between ESG and total factor productivity (TFP). Using data of Chinese listed companies over the period of 2010–2020, we find that there is a positive relationship between ESG performance and TFP. Additionally, ESG improves corporate TFP through reducing the financial constraints and improving the innovation input. Our extended analysis reveals that this beneficial effect tends to be stronger for SOEs (state-owned-enterprises) and industry with high pollution levels. This study has some implications for Chinese firms in relation to their ESG practices and sustainable development.